Beyond nPDFs effects: prompt J/ψ and ψ(2S) production in pPb and pp collisions - Oh, Geonhee; Sirunyan, A. M.; Tumasyan, A. R.; Adam, Wolfgang; Ambrogi, Federico; Md. Ali, Mohd. Adli (Elsevier B.V., 2019)
A multi-dimensional analysis of prompt charmonia in pp and pPb collisions at sNN=5.02TeV with the CMS detector is presented. The pPb differential cross-sections of prompt J/ψ are shown in a wide kinematic region, for transverse momentum pT spanning from 2 to 30 GeV/c and a rapidity interval between -2.4 to 1.93 in the center of mass of the collision. The final results on prompt ψ(2S) meson production cross section in pp and pPb collisions at 5.02 TeV are also reported as a function of pT and rapidity, for pT from 4 to 30 GeV/c. The nuclear modification factor is found to be smaller than that of prompt J/ψ in all measured bins, especially at low pT and at backward rapidity. Such a different behaviour between the ground and excited states cannot be reproduced considering nPDF effects alone. © 2018